Memantine Augmentation Improves Symptoms in Serotonin Reuptake Inhibitor-Refractory Obsessive-Compulsive Disorder: A Randomized Controlled Trial - Modarresi, Atieh; Sayyah, Mehdi; Razooghi, Setareh; Eslami, Kaveh; Javadi, Mohammadreza; Kouti, Leila (Pharmacopsychiatry, 2018)
Introduction There is a large body of evidence on the clinical benefits of augmentation therapy with glutamate-modulating agents, such as memantine in reducing OCD symptoms.Methods A double-blind, placebo-controlled trial was conducted on SRIrefractory OCD patients. Thirty-two patients were randomized to receive either 20 mg/day memantine or placebo augmentation and were visited at baseline and every 4 weeks for 12 weeks. Results were measured using the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS).Results The Y-BOCS total score was significantly reduced in the memantine group at the end of weeks 8 and 12, while no improvement was observed in the placebo group throughout the trial. A reduction of 40.9% in the mean Y-BOCS total score by week 12 in the memantine group resulted in 73.3% of patients achieving treatment response. The findings showed that a time to effect of 8 weeks was necessary to observe significant improvement in OCD symptoms, while treatment response was only seen after 12 weeks of memantine augmentation.Discussion Memantine is an effective and well-tolerated augmentation in severe OCD patients refractory to SRI monotherapy.